Acellular Dermal Matrix Prevents Esophageal Stricture After Full Circumferential Endoscopic Submucosal Dissection in a Porcine Model - Zhang, Baozhen; Zhang, Yue; Wang, Yidan; Yang, Fan; Sheng, Shiyun; Wang, Zhe; Chang, Xiaoying; Wei, Jianyu; Guo, Jintao; Sun, Siyu (Frontiers in Bioengineering and Biotechnology, 2022)
Esophageal stricture is a common complication after endoscopic submucosal dissection (ESD), especially in full circumferential ESD. This study investigated fully covered self-expanding metal stent (FCSEMS) placement with an acellular dermal matrix (ADM) for preventing post-ESD esophageal stricture. Twelve Bama minipigs were randomly divided into two groups, which underwent full circumferential ESD in the distal esophagus. In group A, an FCSEMS with ADM was placed at the mucosal defect, whereas group B underwent standard FCSEMS placement. The stent was removed during gastroscopy 2 weeks after the ESD procedure. At the fourth week, gastroscopy was repeated to evaluate local healing and stenosis. The animals were sacrificed, esophageal specimens were obtained for macroscopic and histological evaluation, and serum C-reactive protein (CRP) levels were quantified. Four weeks post ESD, dysphagia occurrence was lesser in group A than in group B. Group A demonstrated lesser esophageal stricture on macroscopic evaluation (21.02 ± 16.65 % vs. 57.41 ± 8.48 %, P = 0.001) in the form of enhanced re-epithelization (99.13 ± 0.98% vs. 96.63 ± 1.64%, P = 0.009), diminished submucosal fibrosis (1117.53 ± 188.83 um vs. 1834.69 ± 421.99 um, P = 0.003), and attenuated inflammatory infiltration (121.00 ± 30.66 vs. 188.17 ± 64.92, P = 0.045). The increase in the serum CRP level was lower in group A than in group B at 4 weeks post-ESD. FCSEMS combined with ADM can enhance re-epithelization in the process of wound healing and significantly reduce the degree of esophageal stenosis after circumferential ESD. This study provided important preclinical findings for subsequent clinical trials.